Volatile constituents of essential oils isolated from leaf and rhizome of Zingiber cassumunar Roxb. - Md. Nazrul Islam Bhuiyan; Jasim Uddin Chowdhury; Jaripa Begum (Bangladesh Pharmacological Society, 2008)
The composition of the essential oil of Zingiber cassumunar Roxb. from Bangladesh was examined by gas chromatography mass spectroscopy (GC-MS). Sixty-four components were identified in leaf oil and 32 components were identified in the rhizome oil, accounting for 94.60% and 98.56% of the total yields, respectively. The main component in leaf oil was sabinene (14.99%), beta-pinene (14.32%), caryophyllene oxide (13.85%) and caryophyllene (9.47%). On the other hand, rhizome oil contained triquinacene 1,4-bis (methoxy) (26.47%), (Z)-ocimene (21.97%) and terpinen-4-ol (18.45%). The compositions of both oils varied qualitatively and quantitatively.